Main-chain flexibility and hydrophobicity of ionenes strongly impact their antimicrobial activity: an extended study on drug resistance strains and Mycobacterium. Issue 40 (15th September 2022) - Kopiasz, Rafał Jerzy; Zabost, Anna; Myszka, Magdalena; Kuźmińska, Aleksandra; Drężek, Karolina; Mierzejewska, Jolanta; Tomaszewski, Waldemar; Iwańska, Agnieszka; Augustynowicz-Kopeć, Ewa; Ciach, Tomasz; Jańczewski, Dominik
Abstract : A high significance of the main chain flexibility and an unexpected effect of hydrophobicity on the biological activity in series of ionenes was observed. The most potent among the tested polycations showed high activity toward clinical bacterial isolates. Abstract : The spread of antibiotic-resistant pathogens and the resurgence of tuberculosis disease are major motivations to search for novel antimicrobial agents. Some promising candidates in this respect are cationic polymers, also known as synthetic mimics of antimicrobial peptides (SMAMPs), which act through the membrane-lytic mechanism. Development of resistance toward SMAMPs is less likely than toward currently employed antibiotics; however, further studies are needed to better understand their structure–activity relationship. The main objective of this work is to understand the cross-influence of hydrophobicity, main-chain flexibility, and the topology of ionenes (polycations containing a cationic moiety within the main-chain) on activity. To fulfill this goal, a library of ionenes was developed and compared with previously investigated molecules. The obtained compounds display promising activity against the model microorganisms and drug-resistance clinical isolates, including Mycobacterium tuberculosis . The killing efficiency was also investigated, and results confirm a strong effect of hydrophobicity, revealing higher activity for molecules possessing the flexible linker within the polymer main-chain.